Legal Analysis of the Participation of the Prosecutor Agency in Eradication of Narcotics Crime - Henry Elenmoris Tewernussa; Arpangi Arpangi; Rakhmat Bowo Suharto (Universitas Islam Sultan Agung, 2022)
The purpose of this study is to examine and analyze the juridical implications of the role of the Prosecutor's Office in the eradication of narcotics. In this paper, the writer uses the normative juridical method with the specifications of analytical descriptive writing. Article 1 paragraph (3) of Act No. 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia states that the action of the public prosecutor is to delegate the case to the competent district court in matters and according to the method stipulated in the criminal procedure law with a request to be examined and decided by a judge at court. The public prosecutor is a prosecutor who is authorized by law to carry out prosecutions and carry out judges' decisions. A prosecutor at the High Prosecutor's Office or at the Attorney General's Office can sue a person if he or she is first appointed to the District Attorney's Office in whose jurisdiction the offense is committed.